Impact of Margin-to-Depth of Invasion Ratio on Oncologic Outcomes in Locally Advanced Oral Cancer Treated With Surgery and Chemoradiotherapy - Ming-Hsien Tsai; Yu-Tsai Lin; Hui-Ching Chuang; Chao-Hui Yang; Tai-Lin Huang; Hui Lu; Wen-Ling Tsai; Chih-Yen Chien; Fu-Min Fang (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. This study aimed to evaluate the prognostic value of the margin-to-depth of invasion ratio (MDR) in patients with locally advanced oral squamous cell carcinoma (LAOSCC) who underwent curative surgery followed by adjuvant concurrent chemoradiotherapy (CCRT).Methods. We analyzed 422 consecutive patients with LAOSCC treated at a single institution between 2007 and 2017. MDR was defined as the ratio of the closest surgical margin (mm) to the tumor depth of invasion (mm). Survival outcomes, including overall survival (OS), cancer-specific survival (CSS), and relapse-free survival (RFS), were assessed. The optimal MDR cutoff was determined by X-tile analysis and validated using repeated k-fold cross-validation.Results. The optimal MDR cutoff for predicting survival was 0.35. Patients with MDR ≥0.35 (high MDR, n=205) demonstrated significantly better 5-year OS (66.1% vs. 47.6%, P